Communication and information technologies annual politics, participation, and production - Robinson, Laura; Cotten, Sheila R.; Schulz, Jeremy (Studies in media and communications ;, 2015)
Sponsored by the Communication and Information Technologies Section of the American Sociological Association, this volume brings together nine studies of the digital public sphere. The contributions illuminate three key areas of digital citizenship, namely political engagement, participation networks, and content production. In the first section, authors address relationships including: new media and efficacy, YouTube and young voters, political interest and online news. In the following section, the contributions speak to the importance of participation in social, scholarly, familial, and support networks. Subsequently, in section three on production, two contributions offers insight into unequal production, more specifically, gendered digital production inequalities and the varied responsiveness of microbloggers to different kinds of media events and issues. As a whole, the contributions revisit old questions and answer important new queries about netizenship and the digital public sphere.